2010
DOI: 10.1021/jp9118502
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Binding to a Nitrite Reductase Induces a Spin Transition

Abstract: The multiheme enzyme nitrite reductase catalyzes a 6-electron reduction of nitrite to ammonia. The reaction is initiated by substrate binding to the free axial position of the high spin penta-coordinated heme active site. The spin configuration of the resulting complex is crucial for discrimination between the heterolytic vs homolytic character of the cleavage of the N-O bond and, therefore, subsequent steps of the catalytic cycle. Here, we report the first experimental evidence, based on resonance Raman spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Previous studies showed that the Escherichia coli and Desulfovibrio vulgaris ccNiR ferriheme 1 active sites undergo high-spin to low-spin transitions upon binding nitrite. 43,44 This transition had a minimal effect on the UV/vis spectrum of the wild-type enzyme, but resulted in substantial changes to its EPR spectrum. 43 S. oneidensis ccNiR showed analogous behavior, so nitrite binding to it was monitored by EPR.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous studies showed that the Escherichia coli and Desulfovibrio vulgaris ccNiR ferriheme 1 active sites undergo high-spin to low-spin transitions upon binding nitrite. 43,44 This transition had a minimal effect on the UV/vis spectrum of the wild-type enzyme, but resulted in substantial changes to its EPR spectrum. 43 S. oneidensis ccNiR showed analogous behavior, so nitrite binding to it was monitored by EPR.…”
Section: ■ Resultsmentioning
confidence: 99%
“…vulgaris, [38][39][40][41][42] indicate that it is likely the NrfHA enzyme complex, rather than the sulfite reductase, that allows D. vulgaris to use nitrite as an electron acceptor. While the sulfite reductase can reduce nitrite, its high affinity for nitrite and a low turnover number for nitrite reduction 25 may inhibit its ability to use nitrite efficiently as a terminal electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theoretical studies by Bykov and Neese, an intramolecular reaction with Tyr 218 in the final step of the nitrite reduction process led directly to the final product, NH 3 . Dissociation of the final product proceeds concomitantly with a change in heme Fe spin state [ 171 , 197 , 198 ].…”
Section: Reaction Mechanism Of Pentaheme Cytochrome C ...mentioning
confidence: 99%